Penafsiran Ayat-Ayat Haji Dan Umrah Dalam Al-Qur'an - Syapri Wanda Pratama; Zulfikar .; Edi Hermanto (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
The Hajj and Umrah are acts of worship that hold a fundamental place in Islam, not only as religious rituals but also as a means of spiritual, social, and universal development of humanity. The Qur'an, as the primary source of Islamic teachings, contains several verses governing the implementation, meaning, and purpose of the Hajj and Umrah, scattered throughout various chapters, particularly Surah Al-Baqarah (verses 196–203), Surah Ali Imran (verses 96–97), and Surah Al-Hajj (verses 26–37). This paper aims to analyze the interpretation of the verses on the Hajj and Umrah through a contemporary exegetical perspective, emphasizing their spiritual, social, and universal dimensions in the context of modern life. This research uses a qualitative-descriptive method with a library research approach. The results show that contemporary interpretations focus not only on ritual and legal aspects but also emphasize individual spiritual transformation, communal unity, social equality, environmental awareness, and the relevance of the Hajj and Umrah as a medium for civilizational dialogue in the era of globalization. Thus, the Hajj and Umrah are understood as multidimensional acts of worship with transformative significance for both individuals and the global community.